ON THE ARTICLE “WEATHERED POTASSIC VOLCANIC ROCKS AS PROTOLITHS OF THE HEMATITIC PHYLLITES OF THE SOUTHERN SERRA DO ESPINHAÇO (MINAS GERAIS)”: A DISCUSSION - Cabral, Alexandre Raphael; de Abreu, Francisco Robério (Geochimica Brasiliensis, 2021)
Chaves and Knauer (2020) have presented three new whole-rock chemical analyses of phyllitic hematite, a unique metamorphic rock of the southern Serra do Espinhaço. Based on their three samples and a selection of other three samples from the literature, Chaves and Knauer have proposed that the geochemical uniqueness of the rock – i.e., high contents of K2O, Al2O3 and Fe2O3, and depletion in SiO2 – would represent a weathered, feldspathoid-rich alkaline basalt. This contribution is a discussion of their new data, the trace-element contents of which are at odds with those of a potassic, mantle-derived volcanic protolith for the hematitic phyllite. Its Nb/Th ratios of ~3 and chondrite-normalised La/Yb ratios of ~9–17, for instance, are typical of the continental crust. We also point out aspects that escaped the attention of Chaves and Knauer (2020), one of which is the ubiquitous occurrence of tourmaline in the hematitic phyllite.